1993
DOI: 10.1002/art.1780360317
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset osteoarthritis linked to the type ii procollagen gene. detailed clinical phenotype and further analyses of the gene

Abstract: Objective. To specify in detail the clinical phenotype in 2 Finnish families demonstrating linkage between the type I1 procollagen gene (COL2A1) and osteoarthritis (OA). We also reevaluated the linkage and screened the exon sequences of the COL2Al gene for mutations.Methods. We used single-stranded conformation polymorphism and denaturing gradient-gel electrophoresis techniques for the analyses.Results. Osteoarthritis (OA) is a very common disease which varies in its manifestations. Although most cases are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 28 publications
0
22
0
4
Order By: Relevance
“…İyi bilinen risk faktörleri arasında yaş, kadın cinsiyet, travma hikayesi ve aile hikayesi yer almaktadır (22)(23)(24)(25) (29). Metakarp bölgesindeki bu lokal kemik kütlesi kaybı iki mekanizmayla açıklanmaya çalışılmıştır.…”
Section: Discussionunclassified
“…İyi bilinen risk faktörleri arasında yaş, kadın cinsiyet, travma hikayesi ve aile hikayesi yer almaktadır (22)(23)(24)(25) (29). Metakarp bölgesindeki bu lokal kemik kütlesi kaybı iki mekanizmayla açıklanmaya çalışılmıştır.…”
Section: Discussionunclassified
“…a Association for early onset OA; 3 Association for joint involvement and disease severity; *G = generalized; Ha = hand; K = knee; H = hip; na = not available; population based study; HT=haplotype, A27=27 repeats;** = permutation based; *** = including Vaes et al 2008, Southam et al 2007; bold font indicates region with linkage finding The first structural genes analyzed were genes coding for major cartilage collagens II, IX, and XI, where mutations causing Stickler syndrome, a mild chondrodysplasia associated with OA, have been identified (for a review, see Robin et al (2010)). Earlier reports suggested linkage between COL2A1 and OA in two large families (Palotie et al 1989;Vikkula et al 1993), and a causal Arg519Cys mutation in the 1(II) chain was identified in OA families (Ala-Kokko et al 1990;Fertala et al 1997). In addition rare sequence variants in the genes for collagens II and XI have been associated with hip/knee OA (Jakkula et al 2005).…”
Section: Candidate Gene Studiesmentioning
confidence: 95%
“…Similarly as in other complex diseases the early genetic studies in OA focused on rare families and genes known to have a biological role in the development and structure of cartilage (Palotie et al 1989;Ala-Kokko et al 1990;Vikkula et al 1993;Jakkula et al 2005). In the 1990s, the introduction of panels of highly informative microsatellite markers evenly covering the genome allowed hypothesis-free screening with no prior knowledge of the gene functions (Petrukhin et al 1993;Straub et al 1993).…”
Section: Genome-wide Linkage Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Popülasyon bazl› ve farkl› ailelerde yap›lan birkaç çal›flmada kromozom 12 üzerin-deki COL2A1 geninin yayg›n OA ile iliflkili oldu¤u gös-terilmifltir. [39][40][41] Örne¤in bir ailede COL2A1'deki tek bir mutasyon, OA's› olan tüm aile fertlerinde saptanm›fl ve OA's› olmayan bireylerde saptanmam›flt›r. COL2A1'deki mutasyon Stickler sendromu ile de iliflkilidir.…”
Section: Kas Gücüunclassified